Seeing is believing - Luis Teixeira (University of West London, 2020)
Critical care nurses are confronted with the limits of human life on a daily basis, facing several bioethical challenges in their clinical practice. This practice requires reflection, but how can this be developed in a safe environment? 'Seeing is believing' is a pedagogical intervention that uses documentary film to effectively promote critical reflection and group discussion amongst critical care nursing students.